การพัฒนาศักยภาพครูตามมาตรฐานการปฏิบัติงานของคุรุสภาที่เหมาะสมต่อครูประถมในสถานศึกษา กรณีศึกษาโรงเรียนอนุบาลวัดปิตุลาธิราชรังสฤษฎิ์ - เอี่ยมพญา, กัญภร; น้อยมณี, นิวัตต์; มั่งคั่ง, พจนีย์ (วารสารปัญญาภิวัฒน์, 2017)
การวิจัยครั้งนี้ มีวัตถุประสงค์ดังนี้ 1) เพื่อศึกษามาตรฐานที่จำเป็นต่อการพัฒนาศักยภาพครูตามมาตรฐานการปฏิบัติงานของคุรุสภา 2) เพื่อศึกษาระดับการปฏิบัติงานของครูตามมาตรฐานการปฏิบัติงานของคุรุสภา 3) เพื่อศึกษาสภาพและปัญหาการปฏิบัติงานของครูตามมาตรฐานการปฏิบัติงานของคุรุสภา กลุ่มตัวอย่างได้แก่ ครูผู้สอนจำนวน 54 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสำรวจ แบบสอบถาม มีค่าความเชื่อมั่น .79 และแบบสัมภาษณ์ สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ค่าร้อยละ ค่าความถี่ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน ผลการวิจัยพบว่า 1) มาตรฐานการปฏิบัติงานของคุรุสภาข้อ 3 มุ่งมั่นพัฒนาผู้เรียนให้เต็มตามศักยภาพ เป็นประเด็นที่ครูให้ความสำคัญมากที่สุด 2) ผลระดับทักษะการปฏิบัติงานสอนของครูทุกตำแหน่ง ค่าระดับการปฏิบัติงานสอนของครู มีค่าเฉลี่ยโดยรวมอยู่ในระดับมาก 3) การศึกษาสภาพและปัญหาการปฏิบัติงานตามมาตรฐานการปฏิบัติงานของคุรุสภา พบว่า สภาพการปฏิบัติงานของครูดำเนินการโดยจัดสอนเสริมในรายบุคคลให้กับนักเรียนที่เรียนรู้ไม่ทันผู้อื่น จัดกระบวนการเรียนรู้โดยกลุ่มเพื่อให้ผู้เรียนได้ช่วยเหลือกัน และให้ผู้เรียนทุกคนได้ทำแบบฝึกหัดเสริมทักษะ ด้านปัญหาการปฏิบัติงานพบว่า ครูมีปัญหาด้านการสอนไม่ตรงสายวิชาเอก จำนวนวิชามากเกินความจำเป็น และครูต้องการอบรมเพื่อพัฒนาทักษะให้ตรงตามความรู้ที่จะต้องนำไปใช้ The objectives of this research were 1) to study the standards required to develop teachers' potential according to the Teachers' Council of Thailand's performance standards suitable for the teachers' performance, 2) to study the level of teachers' performance according to the Teachers' Council of Thailand's performance standards suitable for the teachers' performance, and to study the conditions and problems of teachers' performance according to the Teachers' Council of Thailand's performance standards suitable for the teachers' performance. The sample group consisted of 54 teachers. The research instruments were survey, questionnaires with Reliability was .79 and interview. The statistics used for data analysis were percentage, frequency, mean and standard deviation were used for data analysis. The research findings were as follows: 1) In terms of the Teachers' Council of Thailand's performance standards, the item 3 of determination to develop every students' potential was the aspect on which the teachers gave the importance the most. 2) In overall, the teachers of all levels gave the importance on the aspect of giving knowledge at an average level. 3) The conditions and Problems of teachers’ Performance according to the Teachers’ Council of Thailand’s performance standard, it was found that the performance of the operations carried out by the teacher were to organize individual tutoring to students who did not know each other, the learning process for the students to help each other, and all students do exercises for enhancing their skills. On the operational problems, it was found that there are the teachers’ problems, about the teaching without serving with their major, the teaching load, and the training for developing their teaching skills.